Small alarmones (p)ppGpp regulate virulence associated traits and pathogenesis of Salmonella enterica serovar Typhi. (9th May 2019) - Dasgupta, Shreya; Das, Sayan; Biswas, Asim; Bhadra, Rupak K.; Das, Santasabuj
Abstract: How Salmonella enterica serovar Typhi ( S . Typhi), an important human pathogen, survives the stressful microenvironments inside the gastrointestinal tract and within macrophages remains poorly understood. We report here that S . Typhi has a bonafide stringent response (SR) system, which is mediated by (p)ppGpp and regulates multiple virulence‐associated traits and the pathogenicity of the S . Typhi Ty2 strain. In an iron overload mouse model of S . Typhi infection, the (p)ppGpp 0 (Ty2ΔRelAΔSpoT) strain showed minimal systemic spread and no mortality, as opposed to 100% death of the mice challenged with the isogenic wild‐type strain. Ty2ΔRelAΔSpoT had markedly elongated morphology with incomplete septa formation and demonstrated severely attenuated motility and chemotaxis due to the loss of flagella. Absence of the Vi‐polysaccharide capsule rendered the mutant strain highly susceptible to complement‐mediated lysis. The phenotypes of Ty2ΔRelAΔSpoT was contributed by transcriptional repression of several genes, including fliC, tviA, and ftsZ, as found by reverse transcriptase quantitative polymerase chain reaction and gene complementation studies. Finally, Ty2ΔRelAΔSpoT had markedly reduced invasion into intestinal epithelial cells and significantly attenuated survival within macrophages. To the best of our knowledge, this was the first study that addressed SR in S . Typhi and showed that (p)ppGpp was essential for optimal pathogenic fitness of the organism.